2014
DOI: 10.1161/strokeaha.114.007028
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Autologous Bone Marrow Mononuclear Stem Cell Therapy for Ischemic Stroke

Abstract: Background and Purpose-Pilot studies have suggested benefit from intravenous administration of bone marrow mononuclear stem cells (BMSCs) in stroke. We explored the efficacy and safety of autologous BMSCs in subacute ischemic stroke. Methods-This was a phase II, multicenter, parallel group, randomized trial with blinded outcome assessment that included 120 patients. Patients with subacute ischemic stroke were randomly assigned to the arm that received intravenous infusion of autologous BMSCs or to control arm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
255
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(276 citation statements)
references
References 14 publications
(18 reference statements)
3
255
0
2
Order By: Relevance
“…37 Moderate to severe ischaemic stroke in the anterior circulation was required for eligibility. Sixty patients were allocated to control and 60 to cell infusion.…”
Section: The Acute or Early Subacute Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Moderate to severe ischaemic stroke in the anterior circulation was required for eligibility. Sixty patients were allocated to control and 60 to cell infusion.…”
Section: The Acute or Early Subacute Paradigmmentioning
confidence: 99%
“…As undertaken in the trial of Prasad and colleagues, 37 bone marrow harvest may be undertaken a few hours prior to administration of cells in the cell therapy arm of a trial, but this permits only use of poorly characterised cells. Ex-vivo culture expansion of more precisely characterised cell types incurs delay that both modifies the potential trial population (to survivors likely to remain hospitalised 1-2 weeks after stroke) and the possible therapeutic effect.…”
Section: Conclusion: Where Next For Clinical Trials?mentioning
confidence: 99%
“…Compared to these other stem cells, MSCs have established a solid safety profile in other disease indications, providing the basis for on-going clinical trials to explore MSCs and their cell subpopulations [73,74]. As noted above, MSCs have been transplanted intracerebrally and peripherally [73,[75][76][77][78], with encouraging pilot studies reporting safety, but efficacy remains to be fully assessed [74].…”
Section: Mscs Their Mechanism Of Action and Safety Profilementioning
confidence: 99%
“…Recent clinical trials on transplantation of MSCs have shown their safety in stroke [75,[79][80][81]. In addition to the small number of patients enrolled in these clinical trials, the translation of laboratory protocols for clinical transplant regimens has been marred with major discrepancies including the lack of well-defined release criteria of the donor cells, varying timing, cell dose and route of transplant intervention, altogether deviating from the established preclinical readouts.…”
Section: Translational Challenges Of Msc Therapy For Strokementioning
confidence: 99%
“…13,14 Guidelines for the conduct of preclinical studies and the design of clinical trials are outlined in the Stem Cell Therapeutics as an Emerging Paradigm for Stroke (STEPS) recommendations, with the aim of ensuring both safety and efficacy outcomes. 15 The prevailing stroke pathology largely dictates the cell delivery route of the transplant regimen.…”
mentioning
confidence: 99%